Parental Satisfaction Regarding Online Education of Their Children During COVID-19 Pandemic - Soti, Harikala; Singh, Nitu Kumari; Sah, Indu; Paudyal, Laxmi (Journal of College of Medical Sciences-Nepal, 2023)
Introduction COVID-19 has emerged as a pandemic and started online education. Online education can play a vital role in the process of teaching and learning and parental satisfaction is extremely important in effective implementation of the online education in their children, especially at homes where newly adopted during COVID-19.The purpose of this study was to assess the parental satisfactions regarding online education of their children during COVID-19 pandemic. Methods This descriptive cross-sectional study was conducted from21st August 2021 to 25th January 2022 in a Phoolbari 11, Pokhara. Ethical approval was taken from the Gandaki Medical College Institutional Review Committee. Purposive sampling method was used. The data were collected using a questionnaire through face to face interview whose children had participated in online education. Results Out of 216 respondents, the study revealed that more than half of the respondents (52.8%) had low satisfaction. The highest satisfaction experienced by parents was social interaction (11.98±2.88) followed by instructional support (14.97±3.11). There was significant association between level of satisfaction with parental sex (p=<0.002), parents’ education (p<0.001), parents’ occupation (p=<0.005), monthly income (p=<0.011) and status of living (p=<0.020). Likewise, there was significant association between level of satisfaction with child sex (p<0.001), fast internet at home for online learning (p=<0.001) and children participate in online class with laptop/tab/mobile phone (p<0.001). Conclusions It is concluded that respondents have low level of satisfaction. Therefore, intervention for increasing satisfaction should be conducted by the concerned authority.